2022
DOI: 10.1177/0143831x211070326
|View full text |Cite
|
Sign up to set email alerts
|

Perceived identity threat and organizational cynicism in the recursive relationship between psychological contract breach and counterproductive work behavior

Abstract: Counterproductive work behavior toward the organization (CWB-O) or supervisor (CWB-S) is commonly treated as a consequence of psychological contract breach (PCB). However, drawing from Self-Consistency Theory, the authors in this article argue that the PCB–CWB relationship is recursive through two mediating mechanisms: self-identity threat and organizational cynicism. Furthermore, the authors predict that the relationship between feelings of violation and CWB-O (or CWB-S) would depend on the extent to which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…This research supports the findings of Qaiser and Abid (2022) that abused nurses typically participate in CWBs when the psychological contract is breached. The significant direct and indirect effect of PCB demonstrated that AS is associated with increased psychological contract breach, which, in turn, leads to a greater likelihood of engaging in CWBs, supporting the mediating role hypothesized in this study and findings align with Griep et al . (2022), and ul Shuja et al ., (2021).…”
Section: Discussionsupporting
confidence: 90%
“…This research supports the findings of Qaiser and Abid (2022) that abused nurses typically participate in CWBs when the psychological contract is breached. The significant direct and indirect effect of PCB demonstrated that AS is associated with increased psychological contract breach, which, in turn, leads to a greater likelihood of engaging in CWBs, supporting the mediating role hypothesized in this study and findings align with Griep et al . (2022), and ul Shuja et al ., (2021).…”
Section: Discussionsupporting
confidence: 90%
“…Thirdly, it becomes clear from analysing the buffering mechanism that there are two (2) primary elements investigated. Personal attributions such as personality (Zhang et al, 2019;Jahanzeb et al, 2020), judgment (Griep et al, 2022), effort (Dahling, 2017;Andel et al, 2022), and cognitive ability (Krishnakumar et al, 2017;Naeem et al, 2020;Newton & Perlow, 2021;De Longis et al, 2022) have been investigated by researchers interested in the internal mechanism. Due to the persistent features and biased impacts of personality on employee behaviour (Weiss & Cropanzano, 1996), it is important to consider factors that influence employees' judgment, effort, and cognitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature review, one of the main sources of affective experiences in the workplace is the unpleasant treatment or unpleasant attitudes of others. For instance, both paid and unpaid workers (Griep et al, 2020) experienced feelings of violation following a breach of a psychological contract (Griep & Vantilborgh, 2018;Griep et al, 2022). Meanwhile, fear, anger, and sadness are just some of the negative emotions that can be triggered in the workplace by mistreatments such as bullying, aggression, and cyberaggression (Fida et al, 2018;Jahanzeb et al, 2020;Paciello et al, 2019;Richard et al, 2020).…”
Section: Unpleasant Treatment/attitudes Of Othersmentioning
confidence: 99%
“…The literature emphasizes the many factors that impact managerial decision-making and ethical behaviour. Managers often encounter challenges when fulfilling their responsibilities, such as the apprehension of facing criticism and being held accountable (Rupp et al, 2017;Griep et al, 2022). Communicating challenging information can strain relationships and impact managerial perceptions of fairness (Mowen et al, 2023).…”
Section: Informationalmentioning
confidence: 99%